If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5) = 4x + 5 Reorder the terms: (5 + x) = 4x + 5 Remove parenthesis around (5 + x) 5 + x = 4x + 5 Reorder the terms: 5 + x = 5 + 4x Add '-5' to each side of the equation. 5 + -5 + x = 5 + -5 + 4x Combine like terms: 5 + -5 = 0 0 + x = 5 + -5 + 4x x = 5 + -5 + 4x Combine like terms: 5 + -5 = 0 x = 0 + 4x x = 4x Solving x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. x + -4x = 4x + -4x Combine like terms: x + -4x = -3x -3x = 4x + -4x Combine like terms: 4x + -4x = 0 -3x = 0 Divide each side by '-3'. x = 0 Simplifying x = 0
| -y^2-4=-y | | 18-7j=-15j-6 | | X-8=4.4 | | 135=10x+10y+xy | | -12+11m=10m | | 12a/4=5 | | 8(4x-5)=11(9+8x) | | -9u+11u=-18 | | Z-10=2 | | 6x+7=28+x+19 | | y=300x+80 | | C+9=9 | | -w+161=74 | | 49=2u+11 | | 11x-16=5x+5 | | -5m-13m=18 | | C+8=5 | | -v+9=293 | | 5y=24/-5y | | -6/u=9 | | 3(x-2)-x(2+3)=3(2x+6) | | 8ax^7(-6ax^6)= | | 143=243-u | | -y^2-3=-3y | | 3v-11=4v | | 2x+30=80 | | 3(7-4x)+3(x-2x)=4 | | 8z+11=2 | | c=-5-4c | | y=-0.8x+3 | | 5x+120=14x-6 | | 42x=1068 |